Gestational Diabetes Mellitus New Developments - Radenković, Miroslav (IntechOpen, 2022)
The incidence of gestational diabetes mellitus (GDM) is increasing, and this pathological condition is strongly associated with some serious adverse pregnancy outcomes and important miscellaneous long-term complications. Therefore, it is important that GDM is timely recognized and adequately managed. Although much knowledge has been acquired regarding the prevention, diagnosis, implications, and management of GDM, the exact mechanisms of its genesis are still under investigation. This book provides a comprehensive overview of recent advances in gestational diabetes mellitus. It includes three major sections directing the reader's attention to the etiology, management, and consequences of the disorder.